Positional benchmarking and team selection based on physical qualities in elite rugby league - Ballard, D. A. (Journal of Australian Strength and Conditioning, 2016)
The purpose of this paper was to present and compare physiological and anthropometrical data across positional groups in rugby league and examine the physical qualities associated in team selection from National Rugby League (NRL) pre-season squads. Over five years, 113 athletes (24.4 + 4.0 years of age) were tested for skinfold thickness, body mass, estimated V ?O2max, 10m and 40m speed, maximal velocity, estimated 1 repetition maximum (1-RM) bench press, chin ups and squat. Players were categorised as NRL, state-based (NSW) or under 20 aged (NYC) playing levels and positional groups (Hit Up Forwards (HU), Adjustables (ADJ) and Outside Backs (OB)). Hopkins Effect Sizes (ES) were used to determine whether these physical qualities influenced team selection. Matched against NSW ADJ, the NRL ADJ had moderately lower skinfolds (50.2mm vs. 64.2mm) and a moderately higher estimated VO2max (58.1 vs. 54.2ml/kg/min). The NRL OB had faster 10 and 40m times and a higher max velocity. Compared to NYC, NRL ADJ had a moderately higher VO2max (58.1 vs. 55.1ml/kg/min). The NRL HU mass (103.6 vs. 97.1kgs), VO2max (56.2 vs. 52.7ml/kg/min) and maximal velocity (8.70 vs. 8.45m/s) were moderately higher and 10m time moderately faster (1.70 vs. 1.76s) than NYC HUs. A large ES was shown for maximal velocity (ES=1.35) and 40m-time (ES=-1.38) for NRL (9.26m/s and 5.01s) and NYC OB`s (8.73m/s and 5.20s) although comparisons of the 10m times showed small ES (ES=-.34). This study not only examined the physical differences between positional groups in elite rugby league but also the specific athletic qualities required to progress into the NRL competition.